2018
DOI: 10.1002/dneu.22629
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of Ears Provides Insights into Inner Ear Afferent Pathfinding Properties

Abstract: Numerous tissue transplantations have demonstrated that otocysts can develop into normal ears in any location in all vertebrates tested thus far, though the pattern of innervation of these transplanted ears has largely been understudied. Here, expanding on previous findings that transplanted ears demonstrate capability of local brainstem innervation and can also be innervated themselves by efferents, we show that inner ear afferents grow toward the spinal cord mostly along existing afferent and efferent fibers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 53 publications
0
15
0
Order By: Relevance
“…If this is the case, Wnt ligands released by the hindbrain could directly bind to inner ear afferents through Fzd3 receptors, facilitating their targeting. Wnt ligands are dorsally expressed in the hindbrain and spinal cord across species 66,67 and previous ear transplantation experiments support the targeting of inner ear afferents to a dorsal source of Wnt 58,64 . Verifying this hypothesis will entail creating neuron specific knockouts of Fzd3 along with identification of the Wnt ligand(s) and its specific source.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…If this is the case, Wnt ligands released by the hindbrain could directly bind to inner ear afferents through Fzd3 receptors, facilitating their targeting. Wnt ligands are dorsally expressed in the hindbrain and spinal cord across species 66,67 and previous ear transplantation experiments support the targeting of inner ear afferents to a dorsal source of Wnt 58,64 . Verifying this hypothesis will entail creating neuron specific knockouts of Fzd3 along with identification of the Wnt ligand(s) and its specific source.…”
Section: Discussionmentioning
confidence: 67%
“…Our previous data indicated that diffusible factors play a substantial role in guidance of central projections of inner ear afferent neurons 58,64,65 . That data, combined with the necessity of Fzd3 and Prickle1 for proper inner ear afferent targeting, suggests Wnt/PCP signaling may be mediating this process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ability to form functional connections with the hindbrain does not depend on the entry point of vestibular ganglion processes into the hindbrain. Functional rerouting to the vestibular nucleus of afferents from transplanted ears that entered into the spinal cord has been demonstrated 138 . Transplantation and rotation of a third ear to generate non-matching stimulation relative to the native ear’s sensory epithelia result in “vestibular dominance columns” 139 .…”
Section: Vestibular Maps For Linear and Angular Acceleration Detectionmentioning
confidence: 99%
“…This suggests the presence of symmetric levels of bilateral utricular afferent activity despite the absence of otoconia with potential, yet so far unknown, consequences for body shape and skeletal organization. Addition of ectopic third ears, either rostrally onto the head (Elliott et al, 2015) or caudally along the tail (Gordy et al, 2018), which imparts asymmetry through supernumerary input, does not appear to produce visible body deformations. This suggests that body symmetry might be correctly established as long as bilateral otolithic signals are available and the signal difference between vestibular neurons on both sides is sufficiently small to be centrally offset through commissural connections (Straka, 2020).…”
Section: Gravitational Forces and The Role Of Otolith Endorgans In Establishing Symmetric Bodiesmentioning
confidence: 99%